2019
DOI: 10.1136/bmjophth-2018-000211
|View full text |Cite
|
Sign up to set email alerts
|

Norrie disease gene polymorphism in Indonesian infants with retinopathy of prematurity

Abstract: ObjectiveRetinopathy of prematurity (ROP) is a major cause of blindness in newborn infants, which also occurs in low-income and middle-income countries. Why ROP progresses in some infants while it regresses in others is still presently unknown. Studies suggest that genetic factors might be involved. Mutations in the Norrie disease (ND) gene are suspected to be related to advanced ROP development. Indonesia is a country with relatively high incidence of ROP, yet the role of these genetic factors in the pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Recently, some studies have used microarray data profiles to illustrate the pathogenesis of ROP [9][10][11][12][13][14], but these studies were based on only a single cohort or single genetic event. To overcome this inadequacy, a comprehensive combination of gene expression profiling techniques and integrative bioinformatics approaches should be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have used microarray data profiles to illustrate the pathogenesis of ROP [9][10][11][12][13][14], but these studies were based on only a single cohort or single genetic event. To overcome this inadequacy, a comprehensive combination of gene expression profiling techniques and integrative bioinformatics approaches should be performed.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In addition, the incidence of ROP is different in different races. [3] This suggested that various changes in the nuclear coding genes might be involved in the occurrence and development of ROP. [2] Familial exudative vitreoretinopathy (FEVR) is an inherited vitreoretinopathy, with clinical manifestations similar to ROP, [4] involving several genes with different variations, including insertions, point mutations, or deletions, which include Frizzled-4 (FZD4), lipoprotein receptor-related protein 5 (LRP5), Norrie disease protein (NDP), and tetraspanin-12 (TSPAN12).…”
Section: Introductionmentioning
confidence: 99%